Design of well-defined shell–core covalent organic frameworks/metal sulfide as an efficient Z-scheme heterojunction for photocatalytic water splitting. Issue 48 (1st December 2021) - Wang, Yan; Hu, Zhao; Wang, Wei; He, Haichuan; Deng, Liu; Zhang, Yi; Huang, Jianhan; Zhao, Ning; Yu, Guipeng; Liu, You-Nian
Abstract : A stable Z-scheme with well-defined architecture by in situ growth of COFs on CdS for photocatalytic water splitting is constructed. The T-COF shell can protect the catalytic center of CdS from deactivation and photocorrosion. Abstract : Development of a covalent–organic framework (COF)-based Z-scheme heterostructure is a promising strategy for solar energy driven water splitting, but the construction of a COF-based Z-scheme heterostructure with well-defined architecture, large contact area and intimate contact interfaces is scarce. Herein, we fabricated a direct Z-scheme heterostructure COF–metal sulfide hybrid (T-COF@CdS) with shell–core architecture by self-polymerization of 1, 3, 5-benzenetricarboxaldehyde and 2, 4, 6-tris(4-aminophenyl)-1, 3, 5-triazine in situ on CdS. The formed C–S chemical bonding between T-COF and CdS could provide a very tight and stable interface. Owing to the properly staggered band alignment, strong interfacial interaction and large interfacial contact area between T-COF and CdS, a Z-scheme route for charge separation and transfer is realized, resulting in electron accumulation in CdS for H2 O reduction. The obtained Z-scheme heterostructure T-COF@CdS-3 exhibits a high apparent quantum efficiency of 37.8% under 365 nm monochromatic light irradiation, and long-term stability arising from shell–core structures in which the T-COF shell protects the catalytic centers of CdS against deactivation, as well as acts as oxidation sites to avoid the photocorrosion of CdS. This work provides a strategy for the construction of a shell–core direct Z-scheme heterostructure photocatalyst for water splitting with high performance.